The Problems of Using Artificial Intelligence in Military Management - Kh. A. Ghazeyan; G. E. Harutyunyan (Управленческое консультирование)
As a state-of-the-art technology, artificial intelligence (AI) claims a key role in improving the well-being and living conditions of human society, as well as in the sustainable development of the global economy, increasing productivity and effectively solving universal problems. Increasingly, questions are also being discussed about the influence of AI — as a new determinant of the balance of power — on the conditions for achieving and maintaining peace in individual regions and around the world. Therefore, the study of modern trends in the use of AI for military purposes (in particular, in the system of military command), as well as the discussion of issues about the possibilities, features and problems of its prospective use, are of great importance in terms of specifying the main guidelines for the preservation and development of the military potential of the state in modern conditions.The purpose of the article is to discuss the application of AI technologies in military control as in terms of possible advantages, and in the aspect of the significant risks associated with the use of AI in the military sphere, and which are universal existential in nature and can have a direct impact on the long-term future of human society — world war between major powers, the possibility of nuclear conflict, and the likelihood of AI spiralling out of control.The theoretical basis for the study was the scientific works of both Armenian and Russian and Western authors.The main research methods are comparative analysis based on observations of various examples of the use of AI in military control and the method of scientific induction, updated taking into account the pragmatic factor (the method of logical inference confirmed by facts).As the results of the study, the article presents the main risks that are possible when using AI for military purposes. In particular, we are talking about a world war between major powers, the likelihood of a nuclear conflict and the withdrawal of AI from control. All these risks are universal existential in nature and can have a direct impact on the long-term future of human society. Some important circumstances and factors are also presented that force more attention to policies to neutralize the risks of using AI in the field of military administration.The conclusions justify the need to comply with the “safety rule” for the use of AI. The formation of a legal framework and relevant infrastructures for this should take place much earlier than the actual use of AI; otherwise, the consequences can be negative rather than positive.